KKN SISDAMAS: OPTIMALISASI PEMBERDAYAAN MASYARAKAT MELALUI PENGGUNAAN SMARTPHONE UNTUK MARKETPLACE - Andang Saehu; Fitriyani Nugraha (Pusat Pengabdian kepada Masyarakat LP2M UIN Sunan Gunung Djati Bandung, 2019)
Comprehensive studies on community empowerment using smart phone in Indonesia, especially in villages in West Java, are still limited. This research is to investigate how the students joining KKN Sisdamas implemented the program of community empowerpent through the use of smarphone for village development in Desa Cikoneng, Kecamatan Ganeas, Sumedang District, West Java. This research adopts the cycles of KKN Sisdaman proposed by Sururie, et al. The data were collected through observation to 30 people using smartphone as ther life screening. The result shows that under the KKN Sisdamas Group 139 are successful in socializing, training, and guiding the community to use their smartphone for trading in marketplaces. There are six groups of trading in different marketplaces that sell different products. Some of which sell T-Shirt souvenirs, kunci, keranjang tahu, and kerecek. The community can operate—sell their own products after having their own accounts in marketplaces. Besides, they also can use some features and applications existing in smartphone to get and share the information through internet browser engine and youtube.